2017
DOI: 10.3892/ol.2017.5750
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular characteristics induced by radiotherapy in rectal cancer based on microarray data

Abstract: Abstract. The present study aimed to reveal the molecular characteristics induced by radiotherapy in rectal cancer at the transcriptome level. Microarray data (ID, GSE26027) downloaded from the Gene Expression Omnibus database were re-analyzed to identify differentially expressed genes (DEGs) between rectal cancer tissues during and prior to radiotherapy. The DEGs were then inputted into the database for annotation, visualization and integrated discovery, an online tool to perform enrichment analyses, and into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In addition, in X-linked adrenoleukodystrophy patients, the combination of methylation levels of SPG20 , UNC45A , and COL9A3 and also the expression levels of ID4 and MYRF would be a good marker for distinguishing the discriminating childhood from adult inflammatory phenotypes [ 24 ]. As for tumor-related research, COL9A3 was identified as tumor suppressor gene in rectal cancer [ 25 ], and it was also significantly associated with the prognosis of triple-negative breast cancer as an independent prognostic signature [ 26 ]. Seldom research about the relationship between COL9A3 and ESCC was taken by now.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in X-linked adrenoleukodystrophy patients, the combination of methylation levels of SPG20 , UNC45A , and COL9A3 and also the expression levels of ID4 and MYRF would be a good marker for distinguishing the discriminating childhood from adult inflammatory phenotypes [ 24 ]. As for tumor-related research, COL9A3 was identified as tumor suppressor gene in rectal cancer [ 25 ], and it was also significantly associated with the prognosis of triple-negative breast cancer as an independent prognostic signature [ 26 ]. Seldom research about the relationship between COL9A3 and ESCC was taken by now.…”
Section: Discussionmentioning
confidence: 99%
“…COL5A3 is a member of the collagen triple helical repeat family and plays a role in cell proliferation, differentiation, apoptosis, migration and carcinogenesis(18). It has been shown to play a key role in breast cancer brain metastases and radiosensitivity in rectal cancer (19,20). Manoj Amrutkar et al found that COL5A3 promotes chemoresistance of pancreatic cancer cells to gemcitabine (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in X-linked adrenoleukodystrophy patients, the combination of methylation levels of SPG20, UNC45A, and COL9A3 and also the expression levels of ID4 and MYRF would be a good marker for distinguishing the discriminating childhood from adult in ammatory phenotypes [24]. As for tumor-related research, COL9A3 was identi ed as tumor suppressor gene in rectal cancer [25], and it was also signi cantly associated with the prognosis of triple-negative breast cancer as an independent prognostic signature [26]. Seldom research about the relationship between COL9A3 and ESCC was taken by now.…”
Section: Discussionmentioning
confidence: 99%